Peran Inovasi Sosial Dalam Percepatan Pembangunan Ekonomi Komunitas - Afiyah Zahrah (FEB Universitas Maritim Semarang, 2025)
Abstract. This study aims to examine the role of social innovation in accelerating community economic development through a participatory approach based on local potential. Social innovation is seen as an effective new solution to address various social and economic problems, particularly at the community level, by involving communities as key actors of change. This study highlights the importance of collaboration between communities, government, academia, the private sector, and non-governmental organizations in creating an inclusive and sustainable development ecosystem. The results indicate that social innovation can strengthen community economic independence, create alternative economic models such as digital cooperatives and community-based economies, and encourage broad participation in the development process. However, various obstacles remain, such as low digital literacy, limited access to funding, and weak policy support. Therefore, systemic interventions and more progressive policy support are needed to expand the impact of social innovation on sustainable community economic development.